AN IMPROVEMENT OF URBAN TRANSPORTATION SYSTEM USING TRANSIT ORIENTED DEVELOPMENT (TOD) METHODS - Suranto Suranto (INFOKUM, 2022)
In Indonesia, there is a problem that always occurs where urban transportation in the Medan area is currently not optimally integrated with the urban transportation network which results in long, inconvenient passenger journeys and high transportation costs. so that in research it is necessary to have an integrated network of urban transportation infrastructure in the City of Medan. in this study using the method of analysis used is descriptive analysis. The current problem of urban transportation in the Medinding region is the absence of optimal integration in the urban transportation network which results in long, inconvenient passenger journeys and high transportation costs. This condition encourages people to use private vehicles